The Impact of the 1999 Education Reform in Poland - Jakubowski, Maciej; Patrinos, Harry Anthony; Porta, Emilio Ernesto; Wisniewski, Jerzy (2012)
Increasing the share of vocational secondary schooling has been a mainstay of development policy for decades, perhaps nowhere more so than in formerly socialist countries. The transition, however, led to significant restructuring of school systems, including a declining share of vocational students. Exposing more students to a general curriculum could improve academic abilities. This paper analyzes Poland s significant improvement in international achievement tests and the restructuring of the education system that expanded general schooling to test the hypothesis that delayed vocational streaming improves outcomes. Using propensity score matching and differences-in-differences estimates, the authors show that delayed vocationalization had a positive and significant impact on student performance on the order of one standard deviation.